The coercive community college bullying and its costly impact on the mission to serve underrepresented populations. - Hollis, Leah P.; Frierson, Henry T. (Henry Taylor), 1944- (Bingley, U.K. : Emerald, 2016)
Few studies address workplace bullying in American higher education. Leah P. Hollis, EdD, author of Bully in the Ivory Tower addressed the issue of workplace bullying in four-year institutions. This volume replicates the study to reveal that 64% of community college respondents are affected by workplace bullying. Women, people of color, and the LGBT community face increased incidents of workplace bullying. This volume addresses topics like the impact of labor unions on higher education workplace bullying. This topic is timely as several unions are emerging for adjunct faculty nationally. Also, the volume offers a rare voice from the presidents perspective on workplace bullying. The narratives show that even the president has a boss, and can be adversely affected by workplace bullying. For those learning about leadership, especially applied to community college, this volume offers ten case studies for discussion and consideration. The volume concludes with a'call to action' for community colleges that have an opportunity to create and maintain a healthy workplace. In turn, effective policy can stop the costly behavior that is eroding the community college mission.
Bruising the bottom line / Leah Hollis -- When the president is bullied / Russell Davis, Leah Hollis -- Color outside the lines / Leah Hollis -- The importance of professor civility in a computer-based open-access environment for a minority serving insitution / Leah Hollis -- Labor intensive / Leah Hollis -- Socially dominated / Leah Hollis -- Insult to injury / Leah Hollis, Sean Robinson -- Cybershaming - technology, cyberbullying, and the application to people of color / Leah Hollis -- Stop bullies in their tracks / Leah Hollis -- Call to action / Leah Hollis.
Includes bibliographical references.
Print version record
Keywords: Education -- Multicultural Education; Higher & further education, tertiary education; Bullying in schools; Bullying in the workplace